Studies in an inflationary economy: the United Kingdom, 1948-1961 - Paish, F. W. (London : Macmillan : New York : St Martin's Press, 1962)
The book examines various aspects of monetary theory, including the determination of interest rates and the Radcliffe Committee's concept of liquidity. It also discusses developments in the internal economic position of the United Kingdom, with special reference to the problems of inflation and its control.
Includes bibliography.
usc 20/09/18
Loans
Keywords: Monetary policy; Inflation (Finance); Great Britain